PENGARUH ETOS KERJA DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA BADAN PEMBERDAYAAN MASYARAKAT, PEMERINTAHAN DESA, PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA KOTA SUNGAI PENUH - Fitrina Afrianti (Jurnal Ekonomi Sakti, 2021)
The aim of this research was to determine how much influence application work ethic and communication in the office of BPMPDPP dan KB Kota Sungai with performance of employee.This research used quantitative method since researcher wanted to determine the measurement of X and Y variable. Population in this study is 32 people. Sampling technique used is a full sampling as many as 32 people. Data analysis techniques in this study ismultiple regresion analysis and coefficient of determination analysis.Questionaires were used as a tool in data collection method. The findings show that all hypothesis were proved to be significant work ethic and communication have a positive and significantinfluence with performance of employee. The implies that played as important rolework ethic and communication (individualy or simultaneously) in developing performance of employee.